Chemical analysis of Weld wire coatings - Kader, Caisy (My University, 2014)
The aim of this project was to get an overall understanding for how different methods of chemical analysis can be applied for analyzing surfaces of weld wires in the welding manufacturing industry. Chemical components mainly focused on consisted of sodium (Na), potassium (K) and calcium (Ca) among other chemical elements. These chemicals are often introduced in lubricants, in dies and in coatings added to the wire surfaces in different phases of the manufacturing process. The reason for performing analytical testings’ during the manufacturing process is that the contents of these chemicals effects the welding properties of weld wires such as conductivity, feedability and arc stability during welding. Through controlling the contents of these chemicals on the wire surfaces it is possible to design welding wires featuring good welding properties, hence optimizing the welding process. However, the main focus of this thesis was dedicated towards studying the different analytical methods generally applied in wire manufacturing process and stayed throughout the project within the scope of this focus. Different analytical measurements were used throughout the analytical tests of these chemicals and consisted of flame atomic absorption spectroscopy (FAAS) and inductively coupled plasma optical emission spectroscopy (ICP-OES). Through interpretation of the ICP-OES analytical data, an overview regarding the lubricant content of Na, K and Ca present on six wire surfaces could be made. Additional analytical methods were also included in the project such as copper bath analysis which can be used for determining the quality of the copper plating solution whereas combustion analysis can be used for providing information regarding the content of organic material existing on the weld wire surfaces. Through applying these different analytical methods it became possible to obtain an outline of the general analytical methods applied in the weld wire manufacturing process and provided a basis for discussing the different analytical methods as well the importance of different stages in the manufacturing process. Data results obtained through the ICP-OES analysis can be used for providing information regarding the contents of lubricant rests and soap rests existing on the surface. The FAAS method is expected to provide similar information as the ICP-OES analysis; however results from the FAAS analysis were observed as inconsistent and did not correlate with previous analytical trials. Combustion analysis and copper plating analysis provide information regarding the content of organic material (C) and copper layer thickness of the surface. Correlations between the contents of different chemicals existing on the surface and the respective welding properties of weld wires were provided through welding tests and discussed with the assistance of chemical experts in the welding area. From the analytical trial analyses it could be concluded that wires with low content of carbon, sodium, potassium and calcium on the surface as well as an even layer of copper coating on the surface shows the best welding features in terms of high conductivity, good arc stability and good feedability. Important stages of the manufacturing process which has an effect on the welding features are the pickling process, drawing /application of lubricant process and the copper plating process. The different analytical methods used in this project proved to be good methods for providing information related to the content of chemicals existing on the surface and also provided good understanding of the chemistry which takes place in vital parts of the manufacturing process.
Keywords: Annan kemiteknik; Övrig bearbetning/sammanfogning; Materialvetenskap; Produktion; Other Chemical Engineering; Other processing/assembly; Materials Science; Production